Tindak Pidana Pembunuhan yang Dilakukan oleh Anak - Gede Widya Arsana; I Made Sepud; I Nyoman Sujana (Warmadewa Press, 2020)
School students are the future generation who still need guidance; if they are failed to be guided, there will be an upheaval in their inner selves that is delinquency, which may turn into a criminal act, like murder. The backgrounds of problems are formulated as follows: 1). what is the judge's consideration in deciding cases of murder committed by the child? 2) How criminal sanctions are imposed on a child? This research uses normative legal research methods. The results show that the rationale judgment of the judges in imposing punishment to the juvenile was merely based on the action of crime committed by the children. The judges only perform their obligations under the Act that has been established and which they assume the verdict was fair for the society and the family victim. However, the judges failed to assume the negative impact of criminal penalties of 10 (ten) years of imprisonment sentenced to the children. It was clear that the judges tend to apply juridical considerations in decision making process. While they did consider the non-juridical considerations in decision Number 22/Pid.Sus.Anak/2016/PN.Tjk which actually should be based on sociological, psychological, criminological, and philosophical of the juveniles. The researcher suggests that: 1) The judges must consider and reconsider the punishment of 10 years imprisonment which may lead to mental decline in children because they are still relatively; 2) The judges shall reconsider the impact that would occur in children as they are living for 10 years in prison.